Calcified gallbladder cancer: is it preventable?. Issue 3 (22nd March 2019) - Thakrar, Reena; Monib, Sherif; Pakdemirli, Emre; Thomson, Simon
Abstract: A case of a newly diagnosed calcified gallbladder cancer is presented, who had pre-existing porcelain gallbladder. Due to the advanced stage of the disease at presentation, the patient had a poor outcome. The investigation and management of gallbladder carcinoma is discussed as well as the relationship with porcelain gallbladder. We conclude that there is only a weak association between porcelain gallbladder and gallbladder cancer, but because gallbladder cancer typically presents late, a stratified approach to offering cholecystectomy to asymptomatic porcelain gallbladder is reasonable.